ANALISIS KOMPARATIF KINERJA KEUANGAN (STUDI PADA CV.NIAGARA SWALAYAN DAN CV. KANJI NIAGA SEJATI BUKITTINGGI) - Najlani Syamsuddin; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine and analyze the level of financial performance of the ratio of liquidity, solvency, profitability and activity. CV. Niagara Supermarkets Bukittinggi and CV. Kanji Niaga Sejati Bukittinggi during the period 2014-2018.This study uses secondary data in the form of data obtained by the author through secondary data in the form of information and information in the form of financial reports obtained from agencies or companies related to this research which are needed by researchers for analysis of liquidity, solvency, and activities.The results of the analysis show that the analysis of the financial statements of CV. Niagara Supermarkets Bukittinggi for the period 2014-2018 based on Liquidity, Solvency, Profitability and Activity Ratios are: 1). Liquidity ratio analysis, the current ratio is in a "good" condition and the quick ratio is in an "not good" condition; 2). Solvency ratio analysis, debt assets ratio was rated "not good", and debt equity ratio was "good"; 3). Profitability ratio analysis, net profit margin got "not good" score and return on equity got "not good" score; 4). Activity ratio analysis, inventory turnover is in "not good" condition, total assets turnover is in "good" condition. While the results of the analysis of financial statements on CV. Kanji Niaga Sejati Bukittinggi 2014-2018 period based on Liquidity Ratio, Solvency, Profitability and Activity 1). Liquidity ratio analysis, the current ratio is in a "good" condition and the quick ratio is in a "good" condition; 2). Solvency ratio analysis, debt assets ratio was rated “good”, and debt equity ratio was “good”; 3). Profitability ratio analysis, net profit margin got "not good" score and return on equity got "not good" score; 4). Activity ratio analysis, inventory turnover is in "not good" condition, total assets turnover is in "good" condition. Based on industry average standards.   Keywords: Comparison of Financial Performance, Liquidity, Solvency, Profitability and Activity